Secretory Carrier Membrane Protein (SCAMP) deficiency influences behavior of adult flies - Zheng, JiaLin C.; Tham, Chook Teng; Keatings, Kathleen; Fan, Steven; Liou, Angela Yen-Chun; Numata, Yuka; Allan, Douglas; Numata, Masayuki (Frontiers in Cell and Developmental Biology, 2014)
Secretory Carrier Membrane Proteins (SCAMPs) are a group of tetraspanning integral membrane proteins evolutionarily conserved from insects to mammals and plants. Mammalian genomes contain five SCAMP genes SCAMP1-SCAMP5 that regulate membrane dynamics, most prominently membrane-depolarization and Ca2+-induced regulated secretion, a key mechanism for neuronal and neuroendocrine signaling. However, the biological role of SCAMPs has remained poorly understood primarily owing to the lack of appropriate model organisms and behavior assays. Here we generate Drosophila Scamp null mutants and show that they exhibit reduced lifespan and behavioral abnormalities including impaired climbing, deficiency in odor associated long-term memory, and a susceptibility to heat-induced seizures. Neuron-specific restoration of Drosophila Scamp rescues all Scamp behavioral phenotypes, indicating that the phenotypes are due to loss of neuronal Scamp. Remarkably, neuronal expression of human SCAMP genes rescues selected behavioral phenotypes of the mutants, suggesting the conserved function of SCAMPs across species. The newly developed Drosophila mutants present the first evidence that genetic depletion of SCAMP at the organismal level leads to varied behavioral abnormalities, and the obtained results indicate the importance of membrane dynamics in neuronal functions in vivo.